Public audit oversight and the originate-to-distribute model - AOBDIA, Daniel (Institutional Knowledge at Singapore Management University, 2021)
The originate-to-distribute (OTD) model, in which the originators of mortgages sell or securitize the mortgages to third parties, likely contributed to the 2008 financial crisis. Auditors were blamed for permitting clients to understate the risks of the model in their financial reports, fostering undisciplined lending. We investigate whether public audit oversight influences OTD lending by promoting more vigilant audits of the financial reports of originators. Using a difference-in-differences design prior to the financial crisis, we find reduced OTD lending by banks after the Public Company Accounting Oversight Board (PCAOB) criticizes their auditors’ audits of financial reports regarding OTD transactions. The reduction is greater for banks with poorer risk controls and stronger incentives to manage earnings. We also find a reduction in gains on loan sales and securitizations. The results suggest that PCAOB inspections can help discipline OTD lending, a real effect of public audit oversight in the United States.